Coeficiente de cultura para o feijão (Phaseolus vulgaris L.) irrigado em plantio de seca - Chartuni Mantovani, Everardo; Chohaku Sediyama, Gilberto; Bernardo, Salassier; Torres Loureiro, Blanor (Revista Ceres, 2025)
This work was carried out to determine the evapotranspiration ratio of an irrigated bean crop (Phaseolus vulgaris L.) for soil and climatic conditions of Viçosa, state of Minas Gerais, with February-March planting, in 16 modified Thornthwaite drainage lysimeters.